(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2026)
The study established an HPTLC fingerprinting profile of sterols and glycosides derived from the methanolic extracts of various plant parts of two halophytic Suaeda species, Suaeda fruticosa Forssk J. F. Gmel. and Suaeda nudiflora (Willd.) Moq. Which are having anti-inflammatory, anti-diabetic and anticancer properties. The comprehensive qualitative phytochemical analyses of water, methanol, chloroform, and ethyl acetate extracts from all parts of Suaeda species revealed the presence of sterols and glycosides, with the methanolic extracts showing the highest amount of both compounds. The chromatographic analysis of methanol extracts was conducted using silica gel 60 F254 HPTLC aluminium sheets with a CAMAG Linomat 5 applicator. The plates were created utilizing a mobile phase composed of chloroform: ethyl acetate (8:12 v/v) for sterols and ethyl acetate: methanol: glacial acetic acid: formic acid (16:1.5:1.5:1 v/v/v/v) for glycosides. Detection of sterols and glycosides on wavelengths at 254 nm and 366 nm before derivatization. After using derivatizing reagent chromatogram detected at 366 nm and 540 nm. Furthermore, the FT-IR analysis confirms the presence of multiple functional compounds. The established fingerprinting will ultimately be invaluable for the identification and differentiation of sterols and glycosides as marker compounds in the two referenced Suaeda species.